anonymous
  • anonymous
Find the equation of the line that passes through the points (-2, 3) and (1, -6). Write your answer in Standard Form. Answer -3x – y = 3 3x + y = -3 3x + y = 3 -3x – y = -3
Mathematics
chestercat
  • chestercat
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

ash2326
  • ash2326
Standard equation of a line passing through points (x1, y1) and (x2, y2) \[ \frac{y-y2}{x-x2}=\frac{y2-y1}{x2-x1}\] here (x1, y1)= (-2, 3) and (x2, y2)= (1,-6) so we have the equation of line passing through \[ \frac {y-(-6)}{x-1}= \frac{-6-3}{1-(-2)}\] we get \[ \frac {y+6}{x-1}= \frac{-9}{3}\] now we have \[ \frac {y+6}{x-1}= \frac{-3}{1}\] cross multiplying we get \[y+6=-3x+3\] so we get \[3x+y=-3\]
ash2326
  • ash2326
option B
anonymous
  • anonymous
the eqn of line is y=mx+c;m=(y2-y1)/(x2-x1);hence m=(3+6)/(-2-1)=9/-3=-3. hence y=-3x+c; put pt(-2,3) as it lies on line and satisfies the eqn hence 3=3*2+c c=3-6=-3; thus eqn of line is 3x+y=-3 optn b

Looking for something else?

Not the answer you are looking for? Search for more explanations.